Delayed Emergence in Pediatric Patients with Neurologic Disease Presenting for Ambulatory Surgery. Issue 3 (March 2018) - Dajani, Khaled; Almualim, Mohammed; Menon, Akshay; Volpi-Abadie, Jacqueline; Lund, Kierstin
Abstract : Objectives: Management of pediatric patients with neurological diagnoses can be challenging for anesthesiologists. We sought to determine whether preexisting neurologic disease could serve as an intrinsic risk factor for prolonged emergence. Methods: Following institutional review board approval, we conducted a database search from 2012 to 2015. Included were patients aged 0 to 18 years undergoing ambulatory procedures, and carrying neurological diagnoses that profoundly affected their development. Patients were excluded if they received a total intravenous anesthetic, were not managed with an endotracheal tube, or were extubated deep. A healthy case-control group also was obtained for comparison. The primary outcome was emergence from anesthesia: time from anesthetic cessation to extubation. Our secondary outcome was time from extubation to discharge. Descriptive statistics were calculated for demographic data, outcomes were analyzed for differences using the Student t test, and regression analysis was performed. Results: Data from 69 patients and 169 controls met criteria. There were no differences between study and control groups for age, sex, procedural length, or intraoperative temperatures. The study group had higher American Society of Anesthesiologists scores (2.4 vs 1.4). The primary outcome of time to emergence was longer in the study group (15.2 vs 11.0 min), and time to discharge also was prolonged (101.0 vs 86.1 min). Regression analysis on most differing variables did not yield a correlation to primary/secondary outcomes, but neurologic disease did correlate to both. Conclusions: In this case-controlled retrospective study, there was a prolongation of anesthetic emergence and hospital discharge times for pediatric patients with severe neurologic disease, mostly independent of external factors. Abstract : Anesthesiologists caring for pediatric patients with severe neurologic conditions frequently report delayed emergence and discharge, but the data are scarce. This case-control retrospective study explores this anecdote, and whether the prolongation is attributable to intrinsic neurologic disease or to commonly known extrinsic factors.